Analisis Pekerjaan Berbasis Kompetensi dalam Manajemen Sumber Daya Insani pada Lembaga Keuangan Syariah: Integrasi Nilai-Nilai Ekonomi Islam - Sri Nurul Nabila; Eka Arlinda Hafid; Lince Bulutoding; Muhammad Wahyuddin Abdullah (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the analysis of work in human resource management (SDI) from the perspective of Islamic economics, especially its application to Islamic financial institutions. This article aims to analyze the implementation of work in human resource management (SDI) in Islamic financial institutions, with a focus on the integration of Islamic economic principles. This study uses a descriptive qualitative approach through literature and case studies in Islamic banks. The results show that systematic and competency-based work analysis is essential in improving the effectiveness of SDI placement, development, and performance assessment. The main findings identify that the application of work analysis that refers to the principles of justice, trust, and social responsibility in accordance with sharia is able to increase professionalism, productivity, and employee job satisfaction. In addition, the integration of Islamic moral values and ethics in work specifications and design has been proven to strengthen a work culture that is oriented towards blessings and mutual benefit. This study recommends that Islamic financial institutions continue to strengthen the process of competency-based work analysis and Islamic values to support superior SDI management.